CHRONIC KIDNEY DISEASE OF UNCERTAIN ETIOLOGY: A SYSTEMATIC REVIEW - Nur Amelia , Devita (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: CKD is a global health issue. Its frequency is 11%–13%. Even though figures aren't available, cases are rising in high-income, low-income, and middle-income countries.3 Most countries' chronic kidney disease (CKD) is caused by diabetes and high blood pressure. Some countries have "nontraditional" CKD causes that are unknown. The Aim: this study want explore about chronic kidney disease (CKD) of uncertain etiology. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 27 articles, whereas the results of our search on SagePub brought up 19 articles. The results of the search conducted for the last year of 2013 yielded a total 8 articles for PubMed and 4 articles for SagePub. In the end, we compiled a total of 11 papers, 9 of which came from PubMed and 2 of which came from SagePub. We included three research that met the criteria. Conclusion: There are several reasons a person can experience CKDu, for example physical conditions such as heat and chemical components such as arsenic.